Analisis Uji Beda Gaya Hidup Mahasiswa Urban dan Rural Terhadap Perubahan Perilaku di Fakultas Kedokteran Universitas Prima Indonesia - Zahrah Fadhilla Nasution; Gusbakti Rusip; Fiska Maya Wardhani (Medan Resource Center, 2023)
This research aims to examine the influence of urban and rural backgrounds on the lifestyle choices and behavioral changes among medical students. The study addresses the question of how different backgrounds shape the students' lifestyles and behavioral patterns. A quantitative approach was employed, involving a sample of 100 medical students (50 from urban areas and 50 from rural areas). Data were collected through a questionnaire and analyzed using a t-test to compare the differences between the two groups. The findings indicate significant variations in lifestyle choices and behavioral changes between urban and rural medical students, with rural students exhibiting higher levels of consumerism and more pronounced behavioral shifts. The study concludes that the students' urban or rural backgrounds play a crucial role in shaping their lifestyles and behaviors, emphasizing the need for contextual considerations in educational interventions and support systems.